Pengaruh Kemudahan, Keamanan dan Kecepatan Layanan terhadap Keputusan Konsumen UMKM di Kabupaten Grobogan dalam Menggunakan QRIS sebagai Alat Pembayaran - Aditya Galuh Dimas Prayoga; Suprayitno Suprayitno (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study is motivated by the rapid growth of digital payment systems in Indonesia, particularly the adoption of QRIS among Micro, Small, and Medium Enterprises (MSMEs). As digital transactions become increasingly essential, understanding the factors influencing consumer decisions to use QRIS is crucial for improving its implementation and acceptance. This research aims to analyze the effects of perceived ease of use, security, and service speed on consumer decisions in using QRIS in Grobogan Regency. This study employs a quantitative approach, with data collected through questionnaires distributed to 115 respondents. The data were analyzed using multiple linear regression to examine both partial and simultaneous effects of the independent variables on consumer decisions. The findings reveal that ease of use, security, and service speed each have a positive and significant effect on consumer decisions. Among these variables, security is identified as the most dominant factor. Simultaneously, all three variables significantly influence consumer decisions, as indicated by a significance value of 0.000 (< 0.05). Furthermore, the Adjusted R Square value of 0.656 shows that 65.6% of the variation in consumer decisions is explained by the three variables, while the remaining 34.4% is influenced by other factors outside this study.